2008
DOI: 10.1159/000151500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Association of Preeclampsia with Polymorphisms of the <i>INS</i>, <i>INSR </i>and <i>IRS1 </i>Genes in Mexican Women

Abstract: Background/Aims: It has been proposed that preeclampsia is a metabolic syndrome of pregnancy. The polymorphisms PstI and MaeIII of INS, NsiI of INSR and Ala513Pro and Gly972Arg of IRS1 have been associated with metabolic syndrome; moreover, the products of these genes are functionally contiguous during insulin signaling. The aim of this study was to assess whether these polymorphisms are associated with preeclampsia. Methods: 46 normotensive pregnant women and 43 preeclamptic patients were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Hyperinsulinemia is harmful and resembles the endothelial dysfunction observed in PE pathophysiology (Muniyappa and Sowers, 2014). An interesting Mexican study evaluating the role of genetic variants of genes involved in insulin responsiveness in PE development focused on: insulin [( INS ); Pst I (rs3842752) and Mae III (rs689)], insulin receptor [( INSR ); Nsi I (rs2059806)], and insulin receptor substrate [( IRS1 ); Ala513Pro (rs1801276) and Gly972Arg (rs1801278)] (Machorro-Lazo et al, 2009). Although no statistical difference in SNPs frequencies was observed, a previous study evaluating different ethnic groups in Mexico observed differences in the Mae II, Pst I, and Nsi I genotype distribution when stratified by fasting insulin and serum triglyceride levels (Flores-Martínez et al, 2004; Sánchez-Corona et al, 2004).…”
Section: Gene Variants Involved In Metabolic Processesmentioning
confidence: 99%
“…Hyperinsulinemia is harmful and resembles the endothelial dysfunction observed in PE pathophysiology (Muniyappa and Sowers, 2014). An interesting Mexican study evaluating the role of genetic variants of genes involved in insulin responsiveness in PE development focused on: insulin [( INS ); Pst I (rs3842752) and Mae III (rs689)], insulin receptor [( INSR ); Nsi I (rs2059806)], and insulin receptor substrate [( IRS1 ); Ala513Pro (rs1801276) and Gly972Arg (rs1801278)] (Machorro-Lazo et al, 2009). Although no statistical difference in SNPs frequencies was observed, a previous study evaluating different ethnic groups in Mexico observed differences in the Mae II, Pst I, and Nsi I genotype distribution when stratified by fasting insulin and serum triglyceride levels (Flores-Martínez et al, 2004; Sánchez-Corona et al, 2004).…”
Section: Gene Variants Involved In Metabolic Processesmentioning
confidence: 99%
“…A previous study of Mexican women, demonstrated that the INSR rs2059806 SNP was not associated with pre-eclampsia (Machorro-Lazo et al, 2009). The association of the SNP with pre-eclampsia in Caucasian women, the association of the SNP with pre-eclampsia only in the presence of SGA in Sinhalese women and the lack of association among Mexican women highlights the importance of the confounding effect of ethnicity on the possible role of genetic variation in multifactorial diseases.…”
Section: Discussionmentioning
confidence: 89%